Sanksi Hukum Terhadap Pelaku Penyelundupan Tenaga Kerja Indonesia (TKI) Secara Ilegal Ke Luar Negeri - A.A Mas Karpeka Devi; Anak Agung Sagung Laksmi Dewi; I Gusti Agung Ayu Gita Pritayanti Dinar (Jurnal Analogi Hukum, 2025)
The lack of job opportunities in Indonesia, along with the increasing needs, has led many Indonesians to choose to seek employment abroad. TKI (Indonesian Migrant Workers) are those who travel abroad to work in order to earn a wage. Individuals who are very enthusiastic about working abroad can create various problems as a result, one of which is the illegal placement of TKI by individuals who send TKI without following the existing regulations. Prospective migrant workers certainly suffer losses due to this situation. Regarding this, (1) What are the legal guidelines for sending Indonesian Migrant Workers (TKI) abroad? What are the legal sanctions for those involved in the illegal trade of Indonesian migrant workers abroad? In this study, a legislative and regulatory approach is combined with a normative legal methodology. Based on the examination, it was found that there may be administrative and criminal sanctions for those who violate the law. However, Law of the Republic of Indonesia Number 18 of 2017 on the Protection of Indonesian Migrant Workers temporarily regulates these sanctions.